ANALISIS PREDIKSI KEBANGKRUTAN PERUSAHAAN TRANSPORTASI MENGGUNAKAN MODEL ALTMAN, GROVER DAN SPRINGATE DI BURSA EFEK INDONESIA - Hidayat, Riskin (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2023)
Bankruptcy is something that must be considered for every company. In Indonesia, currently there are many companies that are expected to experience bankruptcy, which occurs in large companies, especially those on a multinational scale, due to debt data that is greater than total assets, especially in transportation companies. The purpose of this study is to analyze bankruptcy prediction using the Altman, Grover and Springate Models on the Indonesia Stock Exchange PT. with reference to signaling theory. The population is 42 transportation companies for the 2018-2021 period, using a purposive sampling method of 25 companies. Hypothesis testing uses an independent sample t-test. The results of the research are; there is no significant difference between the Altman and Grover models, there is no significant difference between the Altman and Springate models, and there is a significant difference between the Springate and Grover models. The results of this study are useful in assisting potential investors in choosing companies through bankruptcy analysis for each company